2011
DOI: 10.18632/aging.100415
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional longevity is associated with decreased reproduction

Abstract: A number of leading theories of aging, namely The Antagonistic Pleiotropy Theory (Williams, 1957), The Disposable Soma Theory (Kirkwood, 1977) and most recently The Reproductive-Cell Cycle Theory (Bowen and Atwood, 2004, 2010) suggest a tradeoff between longevity and reproduction. While there has been an abundance of data linking longevity with reduced fertility in lower life forms, human data have been conflicting. We assessed this tradeoff in a cohort of genetically and socially homogenous Ashkenazi Jewish c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 22 publications
(37 reference statements)
2
33
0
1
Order By: Relevance
“…Evolutionary theories of aging support a tradeoff between fertility and survival (64), with associations between reproduction and life span being observed in both animal models (37,65,66) and humans. Centenarian women, for example, are more likely to have borne children late in life than women who died at an earlier age (67,68). Furthermore, according to data from historical population databases, late ability to reproduce is associated with improved survival not only in the women (69) but also in their male family members (70), which supports the hypothesis that late fertility and slower somatic aging might share underlying genetic determinants.…”
Section: Reproductive Phenotypes and Longevitymentioning
confidence: 71%
“…Evolutionary theories of aging support a tradeoff between fertility and survival (64), with associations between reproduction and life span being observed in both animal models (37,65,66) and humans. Centenarian women, for example, are more likely to have borne children late in life than women who died at an earlier age (67,68). Furthermore, according to data from historical population databases, late ability to reproduce is associated with improved survival not only in the women (69) but also in their male family members (70), which supports the hypothesis that late fertility and slower somatic aging might share underlying genetic determinants.…”
Section: Reproductive Phenotypes and Longevitymentioning
confidence: 71%
“…First, although high parity in humans is the primary metric to test trade-offs between reproduction and longevity, there is a mixed evidence as to the effects of women bearing 2-4 children, suggesting perhaps a U-shaped relationship with significant effect for high parity, compared with 1 child or P5 children [112]. Second, as is evident in both nonhuman and human data, the effect of reproduction on aging processes may be especially evident at a young age [63,70,[113][114][115]; thus age at first reproduction may be a critical factor in evaluating the two-hit model of increased senescence and reduced longevity. Studies evaluating the effect of early-life abuse and teenage pregnancy should be well-positioned to test the hypothesis presented here [116].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even though accelerated development may prove detrimental to health and even longevity in the longer term, such costs are regarded as ones which natural selection would discount, according to lifehistory theory, given the primacy placed on reproductive success [55,[58][59][60]. Consistent with such a life-history perspective is long-standing evidence that earlier timing of reproduction and shorter lifespans are related across taxa [61], including birds and mammals [13], as well as primates [14] and humans [62,63], although, as noted earlier, inconsistencies exist in the latter case [15][16][17]. Such data become especially noteworthy if the biological processes involved in linking reproduction and lifespan play a role in regulating developmental rate, reproduction and aging, which is exactly what we are predicting.…”
Section: Hit Twomentioning
confidence: 99%
“…Tabatabaie (12) reported that exceptionally long-lived adults had late sexual maturation. In addition, women who reached puberty before 11 years of age had a 20% higher all-cause mortality compared to women who reached puberty at 17 years of age (13).…”
Section: Early Sexual Maturationmentioning
confidence: 99%